Development of optimized palm fatty acid distillate-containing medium for biosurfactant production by Pseudomonas sp. LM19 - Abdul Hamid, Nurfarahin (2019)
The issues regarding biosurfactants arose from the utilization of costly substrate with low product yield leads to the overall production cost to be pricey. Hence, the development of the biosurfactant production medium using a cheap substrate through a combination of various approaches could aid in solving these issues. On the other hand, free fatty acid (FFA)-containing substrates are well-known substrates in the formation of biosurfactants. Since palm fatty acid distillate (PFAD) is considerably cheap, readily available from the mill and contained a significant amount of FFA, it could be one of the potential substrates for biosurfactant production. Therefore, the objective of this study was to develop the PFAD containing medium for biosurfactant production by Pseudomonas sp. LM19 using the combination of traditional and statistical approaches. The process parameters of selected medium were screened and optimized, accordingly using One-Factor-At-Time (OFAT), Plackett Burman Design (PBD) and response surface methodology (RSM) to enhance biosurfactant production and the cell growth. The process parameters of selected modified Bushnell-Haas (BH) medium were further screened in which 6% (v/v) of inoculum size, 1% (v/v) of PFAD and 1.5 g/L of yeast extract have resulted in 2.63 folds increment of biosurfactant production with final emulsification index (E24) of 59.62%. Through PBD, four significant factors were identified; KH₂PO₄, yeast extract, MgSO₄.7H₂O, sodium-EDTA which affecting both biosurfactants productivity and cell number. The optimized production medium containing 1.148% (v/v) PFAD; 4.054 g/L KH₂PO₄; 1.30 g/L yeast extract; 0.023 g/L sodium-EDTA; 1.057 g/L MgSO₄.7H₂O; 0.75 g/L K₂HPO₄; 0.20 g/L CaCl₂.2H₂O; 0.080 g/L FeCl₃.6H₂O resulted in 3.55 folds of increment in responses, biosurfactant productivity (0.3463 g/L/day) with 8.5 ± 0.47×10⁹ CFU/mL of cell generation after seven days of incubation compared to unoptimized production media. The experimental value generated for both responses were almost similar to the predicted RSM value. On the other hand, a majority about 54.18% of dirhamnolipid (RRC₁₀C₁₀) and 39.94% of monorhamnolipid (RC₁₀C₁₀) optimized medium. Above all, manipulation of palm oil by-products such as PFAD proved to be a feasible substrate to increase biosurfactant production. The combination of both traditional and statistical design for the development of biosurfactant production medium could enhance biosurfactant productivity with optimal cell concentration. These ideas may aid in reducing overall production cost and promote their applications for various industries.